2016
DOI: 10.1080/00224499.2016.1143440
|View full text |Cite
|
Sign up to set email alerts
|

How Condom Discontinuation Occurs: Interviews With Emerging Adult Women

Abstract: We have almost no data on how and when couples stop using condoms. This qualitative study investigated the process of condom discontinuation. From November 2013 to April 2014, a total of 25 women living in a college town in the Midwest, ages 18 to 25, participated in semistructured interviews centered around three domains: partner interactions, contraceptive use, and sexually transmitted infection (STI) prevention. Analysis followed a critical qualitative research orientation. Participants described actively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
4
14
0
1
Order By: Relevance
“…A study of 375 African-Americans, ages 14-18 years, found similar results, stating that less frequent communication with their partners about sexual health and the belief that they were in a mutually monogamous relationship predicted inconsistent contraceptive use (Davies et al, 2006). This is consistent with findings from interviews of women, ages 18-25 years, in the Midwest that found that women reported that they discontinued condom use over a period of "nonverbal communication and sporadic use" (Mullinax et al, 2016). In other words, while some young women and their partners start the relationship using condoms, over time they become less consistent but do not have a deliberate discussion about when they want to stop using condoms.…”
Section: Perceived Barriers To Communicationsupporting
confidence: 66%
“…A study of 375 African-Americans, ages 14-18 years, found similar results, stating that less frequent communication with their partners about sexual health and the belief that they were in a mutually monogamous relationship predicted inconsistent contraceptive use (Davies et al, 2006). This is consistent with findings from interviews of women, ages 18-25 years, in the Midwest that found that women reported that they discontinued condom use over a period of "nonverbal communication and sporadic use" (Mullinax et al, 2016). In other words, while some young women and their partners start the relationship using condoms, over time they become less consistent but do not have a deliberate discussion about when they want to stop using condoms.…”
Section: Perceived Barriers To Communicationsupporting
confidence: 66%
“…Use of modern reversible contraception has been shown to prevent unintended pregnancy [3] and short inter-pregnancy intervals, both of which lead to adverse health consequences for mothers and infants [4][5][6][7][8]. While there are several facilitators of contraceptive use, high-quality interpersonal communication from FP providers including counselling on proper use and side-effects [9][10][11][12][13][14], clarification of misconceptions [15,16], and addressing spousal dynamics like covert use and couple communication [17][18][19] are associated with contraceptive uptake and continuation among women [20].…”
Section: Introductionmentioning
confidence: 99%
“…The consistent and correct use of condoms effectively prevents both pregnancy and sexually transmitted disease (STD), and vasectomy is a simple and reliable method of permanent contraception, but these methods cannot meet the different needs of all users (Li, Shao, & Wang, ; Stover et al., ). Allergic reaction, discomfort during use and condom breakage are the main reasons for terminating condom use (Mullinax et al., ; Rana et al., ). Vasectomy is safe, simple and highly effective, and uptake has been identified as one of the indicators of male involvement in family planning.…”
Section: Introductionmentioning
confidence: 99%